Who will grab my land?The Office du Niger, from international investments to local land arrangements. - (:unkn) unknown (My University, 2014)
The 2008 global food crisis led to a wide dynamic of large scale investments in agriculture. In West Africa, the Office du Niger (ON) irrigation scheme is a significant example of such a dynamic of investment in agriculture. 45,000 family farmers grow rice on 100,000 hectares where they have never obtained property rights. Facing low national investment capacity and a significant decrease in the international development assistance, the Malian State launched an appeal to investors to reach the objective defined in the early 1930’s of one million hectares developed for irrigation. Investors were national or foreign investors from the private or public sectors. The State defined new rules to make their access to land easier. The risk of land grabbing linked to the arrival of new investors gave the signal for a rush to access to land in which different actors: investors, farmers, national or local officers, used informal arrangements.This research shows that these arrangements are historically rooted in the evolution of land management in the ON area. The main methodological contribution of this research is that arrangements are analyzed as a process that enables the different actors to adapt to binding rules, and finally to achieve their objectives. Three types of arrangements are described: cooperative arrangements, neo-customary arrangements, and speculative arrangements. By analyzing stakeholders’ games, this research highlights the importance of the actors’ positions and the socio-political context as key factors in the creation of new land arrangements.
Keywords: African Research